Answer:
84
Step-by-step explanation:
Answer:
-1/4 (2x - 5y)
Step-by-step explanation:
For us to factor -1/4 out of -1/2x -5/4y
We will have to multiply the values in bracket by the reciprocal of -1/4 i.e -4 as shown
-1/2x - 5/4 y
= -1/4 (-4(-1/2x) - (-4)(-5/4y))
= -1/4 (4/2 x - 20/4 y)
= -1/4 (2x - 5y)
Hence the factored expression is -1/4 (2x - 5y)
Answer:
1.2
Step-by-step explanation:
(0.85 + 0.50 + 0.15) - 0.30 Given
Simplify by adding in the parentheses first
(0.85 + 0.50 + 0.15) - 0.30
(1.35 + 0.15) - 0.30
(1.5) - 0.30
Subtraction Property
1.5 - 0.30
1.2
Answer:
9.2, 11/12, 91.7, 91.6, .91
Step-by-step explanation:
Answer:
x = 2/15
Step-by-step explanation:
first, create a formula or expression
16x - 7 = x - 5
move x, subtract it
15x - 7 = -5
add 7
15x = 2
divide by 15
x = 2/15
sub in to check:
-4.85667 = -4.86667